Penerapan Notifikasi Pada Android Terhadap Layanan Pelanggan Di Dealer AUTO 2000 - Hariyanto Wibowo; Ketut Artaye; Septilia Arfida; Pikri Pit Pratama (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
The science of information and communication technology, especially the use of mobile devices is currently growing rapidly every year. Where is the growth and consumption rate of more and more information. Along with the times, where mobile devices are a necessity that must be owned by everyone to do various things such as communication, exchanging information and doing other things. One of the operating systems for mobile devices today is Android, where the technology is open source so that get a lot of support. Auto 2000 Way Halim is one of the car dealers in Lampung by providing car service services as well as providing car service car sales and installation of various original spare parts for car vehicles required by customers. Where there are some shortcomings in the company's operational activities, namely still using conventional processes and not implementing mobile technology. When the customer wants to know when to have regular service done, the customer must come directly to the company location. Most customers often ignore periodic service and are often late or not on time in carrying out periodic services. This study uses the Prototype model software development method with the stages of gathering requirements, designing and evaluating the prototype. The results of this study are Notification application which is a medium for delivering information on services at dealers in the form of information about when to perform vehicle service regularly so that it can provide good service for Auto 2000 dealer customers by utilizing Android technology. Key words: Periodic Service, Notification Application, Android.